2009
DOI: 10.1111/j.1467-8624.2009.01313.x
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Neural Correlates of Anticipated Peer Evaluation in Adolescence

Abstract: Neural correlates of social-cognition were assessed in 9-to-17-year-olds (N = 34) using functional magnetic resonance imaging. Participants appraised how unfamiliar peers they had previously identified as being of high or low interest would evaluate them for an anticipated online chat session. Differential age-and sexrelated activation patterns emerged in several regions previously implicated in affective processing. These included the ventral striatum, hippocampus, hypothalamus, and insula. In general, activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
226
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(242 citation statements)
references
References 79 publications
16
226
0
Order By: Relevance
“…A similar pattern of results was seen in an fMRI study using a more ecologically valid 'chatroom' task in which social stress is created by participants being rejected by virtual peers, relative to being accepted (Guyer et al, 2009). Adolescents are likely to encounter peer rejection in everyday life, and may show greater sensitivity to its effects than do adults (Sebastian et al, 2010a).…”
Section: Page 26 Of 49supporting
confidence: 71%
See 1 more Smart Citation
“…A similar pattern of results was seen in an fMRI study using a more ecologically valid 'chatroom' task in which social stress is created by participants being rejected by virtual peers, relative to being accepted (Guyer et al, 2009). Adolescents are likely to encounter peer rejection in everyday life, and may show greater sensitivity to its effects than do adults (Sebastian et al, 2010a).…”
Section: Page 26 Of 49supporting
confidence: 71%
“…There have also been several studies which have looked at the neural bases of typical adolescent responses to peer rejection in the absence of an explicit instruction to regulate (Guyer et al, 2009;Masten et al, 2009;Sebastian et al, 2011), although participants are fully aware of being rejected and of the negative emotions generated, meaning participants may use explicit regulatory strategies spontaneously. One longitudinal fMRI study explored relationships between neural responses to social rejection and depressive symptoms one year later in 20 13-year olds .…”
Section: Page 26 Of 49mentioning
confidence: 98%
“…For example, researchers have investigated how children respond to potential future interaction (e.g. Guyer et al, 2009Guyer et al, , 2012, how adolescents make decisions when observed (Chein et al, 2011), and how children respond to social rejection (e.g. Bolling et al, 2011;Will et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Turning to paradigms that measure participants' automatic regulatory responses to more complex socially provocative stimuli (f. ex. tasks that simulate online social exclusion), these have found more extensive differences occurring in the insula, anterior cingulate cortex (ACC) and medial and lateral functional subdivisions of the PFC between children, adolescents and adults (e.g., Gunther Moor et al, 2010Moor et al, , 2012Guyer et al, 2009;Lau et al, 2011a,b;Masten et al, 2009;Sebastian et al, 2011). However inconsistencies in the directionality of these differences across studies makes drawing interpretations about developmental change difficult.…”
Section: How Does the Importance Of Peers Change In Adolescence?mentioning
confidence: 96%
“…Tasks that present more dynamic social exchanges have replicated and extended these data (e.g., Jarcho et al, 2013a,b). For example, studies using the 'Chat Room Task' (e.g., Guyer et al, 2009), which presents participants with photographs of peers that the participant either 'accepted' or 'rejected' for online interactions in a previous session, have found differential responses in both, anticipation and postevent processing. When anticipating feedback from the previously 'rejected' peers, adolescents with social concerns manifested greater amygdala activity relative to non-anxious adolescents.…”
Section: G Modelmentioning
confidence: 98%